Evaluating the Need For An Analytical Model of Correlated mm-Wave Channels of 5G For Mobility-Related Scenarios - Mirza Mohd Ahsen Baig (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Communication with the millimeter-wave (mm-Wave) is one of the new features present in the fifth generation (5G) mobile networks. The possibility and challenges related to a large population have encouraged many study-based studies to evaluate proposed solutions. Communication in millimeter waves is one of the following Great innovations of the 5G mobile network. For a big reason: Available bandwidth value. However, a millimeter-wave channel given the nature of harsh distribution and sensitivity to congestion. Therefore, the correct modeling of mm-Wave channels is the basis for obtaining accurate results in the simulation of the mm-Wave mobile system. The quality of the mm-wave simulation depends on the channel model, but the favorite channel models of millimeter waves such as the spatial channel model (SCM) have advanced computer density and reduce the density of the solution. End-to-end, systematic development and research. This paper gives an informative exercise in the mm-Wave full-grown section included in ns-3 open source testing system. The module incorporates a variety of models as well as the ability to combine real-time measurements or radiation tracking data. This paper provides equal distribution of a few measurements, for example, SINR in very big cases. We also provide pieces of information on the use of cases where using an easy model can produce the official outcome.